Selective Visualization of Water in Fuel Cell Gas Diffusion Layers with Neutron Dark-Field Imaging. Issue 2 (1st January 2019) - Siegwart, M.; Harti, R. P.; Manzi-Orezzoli, V.; Valsecchi, J.; Strobl, M.; Grünzweig, C.; Schmidt, T. J.; Boillat, P.
Abstract : Visualizing the water distribution in porous gas diffusion layers (GDLs) of operating polymer electrolyte fuel cells (PEFCs) is indispensable to understand the impact of water management on performance. For this purpose, neutron and X-ray transmission imaging have been used for nearly two decades. Certain limitations inherent to attenuation based imaging methods can be overcome by applying neutron dark-field imaging, which has the ability to selectively visualize structures in the micrometer size range. In this study, we compare dark-field images and transmission images of GDLs filled with water through an injection channel. The high contrast of the dark-field value between a heavy water filled and a dry GDL is suitable to reveal water distribution patterns in the GDL. The water present in the 1 mm wide water injection channel of the test device does not alter the dark-field signal, as this technique is selectively sensitive to microstructures. Therefore, neutron dark-field imaging can be applied for the selective analysis of the water distribution in the GDL overlapping with channel water. In addition to the selective visualization of water distributed in a GDL, we show that neutron dark-field imaging can also be used to visualize GDL damages.